Building the Frequency Profile of the Core Promoter Element Patterns in the Three ChromHMM Promoter States at 200bp Intervals: A Statistical Perspective - Heather Lent; Kyung-Eun Lee; Hyun-Seok Park (Genomics & Informatics)
Recently, the Encyclopedia of DNA Elements (ENCODE) Analysis Working Group converted data from ChIP-seq analyses from the Broad Histone track into 15 corresponding chromatic maps that label sequences with different kinds of histone modifications in promoter regions. Here, we publish a frequency profile of the three ChromHMM promoter states, at 200-bp intervals, with particular reference to the existence of sequence patterns of promoter elements, GC-richness, and transcription starting sites. Through detailed and diligent analysis of promoter regions, researchers will be able to uncover new and significant information about transcription initiation and gene function.